Free-radical gases on two-dimensional transition-metal disulfides (XS2, X = Mo/W): robust half-metallicity for efficient nitrogen oxide sensors - Zhang, Chunmei; Jiao, Yalong; Ma, Fengxian; Kasi Matta, Sri; Bottle, Steven; Du, Aijun (Beilstein Journal of Nanotechnology, 2018)
The detection of single gas molecules is a highly challenging work because it requires sensors with an ultra-high level of sensitivity. By using density functional theory, here we demonstrate that the adsorption of a paramagnetic unpaired free radical gas (NO) on a monolayer of XS2 (X = Mo, W) can trigger the transition from semiconductor to half metal. More precisely, the single-layer XS2 (X = Mo, W) with NO adsorbed on it would behave like a metal in one spin channel while acting as a semiconductor in the other spin orientation. The half-metallicity is robust and independent of the NO concentration. In contrast, no half-metallic feature can be observed after the adsorption of other free radical gases such as NO2. The unique change in electronic properties after the adsorption of NO on transition-metal sulfides highlights an effective strategy to distinguish NO from other gas species by experimentally measuring spin-resolved transmission. Our results also suggest XS2 (X = Mo, W) nanosheets can act as promising nanoscale NO sensors.
Keywords: free radical; half-metallicity; nitric oxide (NO); sensors; spin-polarized